Vibrio metschnikovii among diarrheal patients during cholera epidemic in Recife Brazil Vibrio metschnikovii entre pacientes diarréicos durante epidemia de cólera no Recife, Brasil - Vera Magalhães; Adeíza Branco; Roberto de Andrade Lima; Marcelo Magalhães (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
Although known since the last century, Vibrio metschnikovii was only appropriately described and recognized as a new species within the genus Vibrio in 1978. Rarely is the organism linked to human disease. Only once has V. metschnikovii been incriminated as responsible for human diarrhea, and affecting an old woman who suffered from diabetes and had a hepatoma. During the first two years of the present cholera epidemic, which reached Recife in March, 1992, we screened for vibrio nearly 4000 diarrheal fecal specimens submitted to a private clinical laboratory for detection of enteropathogenic microorganisms. Now, we report six cases of diarrhea associated with V. metschnikovii affecting individuals not suffering of any apparent underlying systemic illness. Embora reconhecido desde o século passado, o Vibrio metschnikovii só foi descrito e classificado de forma apropriada dentro do gênero Vibrio em 1978. Raramente, essa bactéria tem sido relacionada com doença humana, acometendo habitualmente, pacientes imunodeprimidos. Há apenas um relato de gastroenterite a V. metschnikovii. Durante a recente epidemia de cólera, que acometeu o Recife em março de 1992, todos os espécimes fecais diarréicos submetidos a um laboratório particular de patologia clínica para diagnóstico microbiológico, foram também cultivados em meio tiosulfato, citrato, sais biliares e sacarose (TCBS). Analizou-se um total de 4000 amostras fecais durante os dois anos que se seguiram a chegada da cólera ao Recife. No presente, reportamos seis casos de diarréia a V. metschnikovii ocorridos nesse período.